(untitled) (Jurnal Teknologi Industri Pertanian, 2016)
Distribution system is part of a logistics system that has a major role for increase the company’s logistic cost. The increase of fuel prices, labor costs, and presence of traffic congestion in Jabodetabek and Bandung area and also to determine the best alternative strategies which viewed from the estimated of the company’s required raw materials on each day, empty capacity of the truck, and also costs incurred on each month. The determine the best alternative distribution strategies, raw material necessity forecasting are needed which will affect the entire capacity of the truck as well as the minimum spanning tree which used to determine the most efficient alternative pathway. After simulation of the company’s distribution channel, then there are three alternative distributions which incorporating with the different combination of pathways. Alternative I determined by changed the distribution channels of each company’s truck, alternative II determined by changed the distribution channels based on the shortest distance of the main warehouse and unify all outlets both inside and outside Jabodetabek and Bandung area into one distribution pathway, and the alternative III determined based on the shortest distance from the main warehouse but separating outlets in outside Jabodetabek and Bandung area into one group. Based on the environmental conditions in Jabodetabek and Bandung which have frequent traffic congestion, the monthly required distribution cost, the empty capacity of each truck, and estimated company needs of marine fish, it can be stated that alternative II is deal alternative and can be used by the company. Keywords: distribution cost, distribution system, forecasting, logistic system, minimum spanning tree